Sulbactam treatment for pneumonia involving multidrug-resistant Acinetobacter calcoaceticus–Acinetobacter baumannii complex. Issue 6 (June 2015) - Lin, Huang-Shen; Lee, Ming-Hsun; Cheng, Chun-Wen; Hsu, Po-Chang; Leu, Hsieh-Shong; Huang, Ching-Tai; Ye, Jung-Jr
Abstract: Background: Multidrug-resistant (MDR) Acinetobacter calcoaceticus – Acinetobacter baumannii (Acb) complex has become an important cause of nosocomial pneumonia. Sulbactam is a β-lactamase inhibitor with antimicrobial activity against MDR Acb complex. Methods: To investigate outcomes of pneumonia involving MDR Acb complex treated with sulbactam or ampicillin/sulbactam for at least 7 days, we conducted a retrospective study of 173 adult patients over a 34 month period. Results: Of 173 patients, 138 (79.8%) received combination therapy, mainly with carbapenems (119/138, 86.2%). The clinical response rate was 67.6% and the 30 day mortality rate was 31.2%. The independent predictors of clinical failure were malignancy, bilateral pneumonia and shorter duration of treatment. In patients with sulbactam-susceptible strains, there was no difference in clinical and microbiological outcome between combination therapy and monotherapy. Compared to the sulbactam-susceptible group, the sulbactam-resistant group had a lower rate of airway eradication, a longer duration of treatment and a higher rate of combination therapy with predominantly carbapenems ( p < 0.05). There was no significant difference between the two groups in clinical resolution and 30 day mortality rates. Conclusions: Sulbactam could be a treatment option for pneumonia involving MDR Acb complex, and combination therapy with carbapenems could be considered for sulbactam-resistant cases.